Nuclear magnetic resonance spectroscopy of copper proteins - Cass,AEG; Hill,HAO (2018)
Of all the techniques currently used to study macromolecules in solution, only nuclear magnetic resonance (NMR) spectroscopy has the power to reveal details of molecular structure and motion at atomic resolution.1–5Though the complexity of the spectra of most molecules of interest makes it difficult to express this power and capitalize on the information provided, recent advances in spectrometer design and data manipulation have considerably extended its range of fruitful applications. Compare, e.g., an early (about 1975) 1H NMR spectrum of azurin with one obtained recently (Figure 1) in which the increased resolution and signal-to-noise ratio are only two of the improved features apparent. Many other advances will be revealed in examples considered in detail later in this chapter. First, we provide a brief description of the object of our spectroscopic attentions and the salient features of the technique for those unfortunate to have not yet made its acquaintance.